(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
ملخص نحاول في هذا المقال استجلاء مبحث مهم في الشعرية؛ وهو شعرية الشخصيات كونها من أبرز التقنيات التي يعنى بها السارد في قصته أو روايته، ولأن الرافعي من الكتاب المجيدين للقص ولو أنه لم يكتب فيها كثيرا، إلا أننا في كتابه كتاب المساكين نلمس توظيفا مناسبا لعنصر الشخصيات الواردة في قصصه من هذا الكتاب، ولأنه يتمتع بقدر سردية غريبة وبديعة تنبع من أسلوبه وأفكاره التي تكون أكثر عمقا وتأثيرا، فسنحاول فهم كيف وظف الرافعي هذه الشخصيات في كتاب المساكين، وما المعاني المختزنة وراء توظيفها بهذا الشكل، وما الذي تؤديه شعريتها خاصة وأنها عنصر من عناصر القصة التي هي شكل من أشكال السرد. كلمات دالة : الشعرية، الشخصيات، الرافعي، السرد، المساكين. Abstract: In this article we try to elucidate an important topic in poetry, which is the poetry of the characters being one of the most important techniques that the narrator is concerned in his story or his novel. Because Al- Rafi’i extending the story, even though he did not write much, but we feel appropriate employment of the characters In his stories from this book, and because it has a strange and exotic narrative, stems from his style and ideas that are more profound and influential. We will try to understand how al-Rafi’i employed these characters in the book of the poor, and the meanings stored behind the employment in this way, and what does this poetry especially as it is an element of the story that is Form of Narrative. Key word: Poetry, Characters, Rafii, Narration, El-massakin.